Adhesive Intestinal Obstruction as One of the Causes of Emergency Conditiond in Children - E. Y. Dyakonova; I. V. Poddubnyi; A. S. Bekin (Педиатрическая фармакология, 2015)
Adhesive intestinal obstruction is one of the reasons of emergency conditions in children. The article discusses the problem of sintered ileus (SKN), from causes to treatment. It stresses the urgency of the problem of timely diagnosis SKN consisting of X-ray, ultrasound and endoscopic methods of investigation. Described are several classifications, based on which not only the differentiation of different types of SKN is carried out, but also the tactics of patients. Conservative methods of SKN treatment in children are presented as well as the use of laparoscopy, when conservative therapy is not effective, not only to evaluate the prevalence of adhesions in the abdominal cavity but also to remove the cause of intestinal obstruction.